2023
DOI: 10.1093/pcmedi/pbad008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and tumor size on the development of the Kasabach–Merritt phenomenon in patients with kaposiform hemangioendothelioma: a retrospective cohort study

Abstract: Introduction The Kasabach-Merritt phenomenon (KMP) is a severe complication of kaposiform hemangioendothelioma (KHE). The risk factors for KMP need further investigation. Methods The medical records of patients with KHE were reviewed. Univariate and multivariate logistic regression models were used for the risk factors for KMP, and the area under the receiver operator characteristic (ROC) curve was used to assess the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the previous studies, there have been many hypotheses regarding the occurrence of KMP, mostly related to lesion sizes, platelet activation, and high expression of podoplanin ( 35 , 36 ). Our previous research revealed that the larger the lesion in KHE patients, the higher the risk of developing KMP ( 37 ). The spleen lesions in all three patients were diffuse.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, there have been many hypotheses regarding the occurrence of KMP, mostly related to lesion sizes, platelet activation, and high expression of podoplanin ( 35 , 36 ). Our previous research revealed that the larger the lesion in KHE patients, the higher the risk of developing KMP ( 37 ). The spleen lesions in all three patients were diffuse.…”
Section: Discussionmentioning
confidence: 99%